Impact of alternate partial root-zone irrigation on the rhizosphere microbiota of alfalfa plants inoculated with rhizobia - Zou, Junhong; Xin, Jianhui; Wang, Tiemei; Song, Qing (Frontiers in Microbiology, 2024)
Water is an important constraint on alfalfa (Medicago sativa) production in arid and semiarid areas, and alternate irrigation in root areas has water-saving potential for alfalfa production. To investigate the impact of alternate partial root-zone irrigation (APRI) on the rhizosphere soil microorganisms of alfalfa, this study subjected alfalfa plants to different irrigation methods and irrigation levels. The growth status and rhizosphere soil microbial community diversity of alfalfa plants under alternate root-zone watering treatment were analyzed through laboratory experiments and high-throughput sequencing. The results showed that at soil moisture levels of 80% field moisture capacity (FMC) and 60% FMC, APRI had no significant impact on the biomass or nodule number of alfalfa. However, 40% FMC significantly reduced the individual plant dry weight, chlorophyll content, and nodule number of the alfalfa plants. APRI increased the relative abundance of Actinomycetes in the alfalfa rhizosphere soil. Moreover, at 60% FMC, the MBC and MBN of rhizosphere, relative abundance of Actinobacteria and unclassified K fungi and Chao 1 index of bacteria significantly increased under APRI treatment. While relative abundance of Ascomycetes and Proteobacteria in the alfalfa rhizosphere significantly reduced under 60% FMC+APRI treatment. In summary, under the same irrigation conditions, APRI did not significantly affect the growth of alfalfa in the short term. And 60%FMC+APRI treatment did significantly affect the groups, structure and diversity of the rhizosphere soil microbial communities.